Real-Time Ultrasound Simulation for Training of US-Guided Needle Insertion in Breathing Virtual Patients. - Mastmeyer, André; Wilms, Matthias; Fortmeier, Dirk; Schröder, Julian; Heinz Handels (Studies in health technology and informatics, 2016)
One draw-back of most existing VR ultrasound training simulators is the use of static 3D patient models neglecting physiological changes induced e.g. by respiration or heart motion. In this paper to the aim of more realistic Ultrasound simulation, breathing motion extracted from 4D CT image data is integrated into our visuo-haptic simulation framework. The simulated ultrasound images are used for the training of US-guided needle insertion procedures in liver surgery. The methodology developed enables US simulation, 3D visualization and haptic steering of the ultrasound probe and the needle in real-time in breathing virtual bodies.